An Investigation of the Problem Solving Strategies used of Middle School Students for of the Assumption Component of Mathematical Thinking - Kükey, Ebru; Aslaner, Recep; Tutak, Tayfun (My University, 2019)
This study aims at scrutinizing the middle school students’ problemsolving strategies with regard to the assumption component ofmathematical thinking. The study is designed as a case study, amongother qualitative research methods. The study group is comprised of 96middle school students. The data in the study are obtained via nonroutine problems prepared for the assumption component ofmathematical thinking. When the strategies the students used insolving the problem are addressed, it is seen that they used theequating, with guess and verify strategies. In this respect, it isconsidered that the students used two of problem solving strategiesand this issue should be paid attention in their education process inorder for them to learn other problem solving strategies.
Keywords: Eğitim; Eğitim Araştırmaları; Matematik